Antecedents of the use of online banking by students in Malaysia: extended TAM validated through SEM - Jan, Muhammad Tahir; Jehangir , Muhammad (2012)
Purpose – The radical advances in the electronic banking technologies have inaugurated unique methods of transaction with a bank, especially using online banking medium. The main purpose of this study is to replicate an extended technology acceptance model (TAM) in order to determine those factors that impact the students’ intention to use online banking, in Malaysian context. Two main banks were selected for data collection purposes, namely, Bank Muamalat Malaysia Berhad and Bank Islam Malaysia Berhad. Design/methodology/ approach – A self-administered questionnaire, which was already developed and tested previously by various scholars, have been adapted for the present study. The questionnaire was distributed through convenience sampling to 550 students of different faculties and universities in Malaysia. A total of 451 usable responses were finally selected for the data analysis purpose. First, the descriptive analysis was undertaken in order to observe the data for various trends. After descriptive analysis, data was inferentially analyzed by deploying Structural Equation Modelling (SEM). The main steps of SEM followed in this particular research were; Confirmatory Factor Analysis (CFA) and full fledge Structural Equation Modelling, which led to hypothesis testing using AMOS computer software. Findings – The results indicate that Perceived Usefulness, Perceived Enjoyment, and Quality of Internet Connection are the main antecedents of the use of online banking by students. Moreover, the Information on Online Banking significantly affects Perceived Ease of Use, and Perceived Enjoyment. Furthermore, Quality of Internet Connection statistically significantly impact Perceived Enjoyment and Security & Privacy. Descriptive statistics indicates 71.8% males and 28.2% females, 46.3% have their accounts in Bank Muamalat Malaysia Berhad and 34.6% in Bank Islam Malaysia Berhad. A total of 90.7% students were in between 15 to 35 years of their age. Most of them (64.5%) were the master’s students of different fields, with majority of them (35.9%) pursuing their MBA. Research limitations/ implications – The use of convenience sampling in this study weakens research objectivity and the relatively small size of the sample somewhat limits generalizations. Originality/ value – The use of complex modelling techniques, namely, Structural Equation Modelling is a novel attempt in validating the extended TAM. Further, this study also extends the understanding of the technology acceptance model from students’ behaviour perspective. Perhaps the model validated in the present research can be adopted by future researchers for further investigation, especially in other countries and industries.